Shiloh - Naylor, Phyllis Reynolds (Naylor, Phyllis Reynolds. Shiloh., 1991)
When he finds a lost beagle in the hills behind his West Virginia home, Marty tries to hide it from his family and the dog's real owner, a mean-spirited man known to shoot deer out of season and to mistreat his dogs.